2006
DOI: 10.1134/s0026893306010055
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of point mutations of the BRCA1 gene by hybridization with hydrogel microarrays

Abstract: Retrotransposon L1 codes for a unique dicistronic mRNA which serves both a transposition intermediate and a template for the synthesis of two proteins of this mobile element. According to preliminary data, the translation initiation of both cistrons of L1 occurs by non-canonical mechanisms. When translating the L1 mRNA in rabbit reticulocyte lysate (RRL), a standard system routinely used by many researchers to study mechanisms of translation initiation in eukaryotes, we observed along with expected products a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…However, in the S30 extract they all have substantial activity. As the relative translation efficiencies in the nuclease untreated S30 extract reflect much better the situation observed in transfected cells, we conclude that RRL is not an adequate system to study the translation initiation mechanisms for mRNAs with complex 5′ UTRs, a conclusion that had been already made in our recent reports (16,17). …”
Section: Resultsmentioning
confidence: 61%
“…However, in the S30 extract they all have substantial activity. As the relative translation efficiencies in the nuclease untreated S30 extract reflect much better the situation observed in transfected cells, we conclude that RRL is not an adequate system to study the translation initiation mechanisms for mRNAs with complex 5′ UTRs, a conclusion that had been already made in our recent reports (16,17). …”
Section: Resultsmentioning
confidence: 61%
“…According to the data of a number of researchers, the BRCA1 5382insC mutation is the most frequent in Russia. For instance, the studies carried out in Mos cow and St. Petersburg showed that the percentage of the BRCA1 5382insC carriage among the BRCA patients constituted 3 to 4% [18][19][20].…”
Section: Frequencies Of the Mutations Examinedmentioning
confidence: 98%